Enhancing Cultural Heritage Preservation: The Role of Artificial Intelligence in Documenting the Pattennung Dance through 360° Video Technology - Jamilah, Jamilah; Sahnir, Nurachmy; Makawi, Faisal Erlangga (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The advancement of Artificial Intelligence (AI) technologies offers novel prospects for the preservation of cultural heritage, particularly in traditional performing arts like the Pattennung dance. Representing a significant aspect of South Sulawesi's cultural identity, Pattennung encapsulates historical, social, and philosophical dimensions inherent in its choreography. However, existing challenges such as inadequate documentation, a decline in participation among younger generations, and the pervasive forces of globalization render this traditional art form vulnerable to cultural dilution and potential extinction. This article examines the multifaceted role of AI in the digitalization and preservation of Pattennung, employing techniques such as motion reconstruction, cultural databases, and immersive Virtual Reality (VR) environments to create engaging and authentic cultural experiences. While these technological innovations provide pathways for broader accessibility and educational opportunities, they also present significant challenges regarding cultural authenticity, including the risks of commodification, the reduction of rich philosophical meanings, and potential distortions of the dance's historical context. This study highlights the importance of integrating community involvement and ethical considerations in the development of AI applications to ensure that the true essence of Pattennung is preserved. By fostering collaboration among cultural practitioners, technologists, and local communities, this research argues that AI can serve as a strategic asset in the enduring effort to uphold and celebrate traditional art forms. The findings of this study aim to inform policymakers and cultural organizations on the best practices for AI implementation in cultural preservation, ultimately ensuring that innovations in technology reinforce rather than undermine the authenticity of cultural expressions. The integration of AI brings both opportunities and challenges, warranting a balanced consideration of techniques like Digital Twin Technology and immersive digital experiences that not only document but also enhance community engagement and intergenerational transmission of cultural knowledge. This research asserts that AI possesses the substantial potential to catalyze cultural preservation efforts while keeping the philosophical and contextual narratives intact, thereby enriching the cultural fabric of society.